2020
DOI: 10.7717/peerj.10000
|View full text |Cite
|
Sign up to set email alerts
|

Cetaceans along the southeastern Brazilian coast: occurrence, distribution and niche inference at local scale

Abstract: It is deemed important to understand cetacean occurrence and distribution to comprehend their ecological roles. The geographical occurrence of species’ niche can be used to better describe their potential distribution. The niche can be defined using environmental variables. Those variables are considered static and not affected by biological activities. The present study goal was to assess the occurrence and distribution of cetaceans along the southeastern Brazilian coast, as well as to define the fundamental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 64 publications
(86 reference statements)
4
7
0
Order By: Relevance
“…The isotopic values estimated for T. truncatus indicate the consumption of coastal/benthic prey and relatively higher trophic position than the other species analysed. This is in agreement with previous studies on the same species in south-eastern Brazil, that also suggested the use of inshore areas along the 16 and 45 m isobaths (Figueiredo et al, 2020;Paschoalini & Santos, 2020) and high trophic level (Bisi et al, 2013). Additionally, stomach content analyses of T. truncatus from south-eastern Brazil showed a great importance of demersal piscivorous fish, such as cutlass fish (Trichiurus lepturus), banned grunt (Conodon nobilis) and Atlantic midshipman (Porichthys The number of skin samples obtained from stranded (STR), incidentally caught (IC) or biopsied (BP) individuals and the total number of samples (N) for each species; Mean (± SD) of C/N ratios, measured and mathematically corrected carbon (δ 13 C and δ 13 C cor , respectively), and nitrogen stable isotopes (δ 15 N).…”
Section: Resident Speciessupporting
confidence: 93%
See 3 more Smart Citations
“…The isotopic values estimated for T. truncatus indicate the consumption of coastal/benthic prey and relatively higher trophic position than the other species analysed. This is in agreement with previous studies on the same species in south-eastern Brazil, that also suggested the use of inshore areas along the 16 and 45 m isobaths (Figueiredo et al, 2020;Paschoalini & Santos, 2020) and high trophic level (Bisi et al, 2013). Additionally, stomach content analyses of T. truncatus from south-eastern Brazil showed a great importance of demersal piscivorous fish, such as cutlass fish (Trichiurus lepturus), banned grunt (Conodon nobilis) and Atlantic midshipman (Porichthys The number of skin samples obtained from stranded (STR), incidentally caught (IC) or biopsied (BP) individuals and the total number of samples (N) for each species; Mean (± SD) of C/N ratios, measured and mathematically corrected carbon (δ 13 C and δ 13 C cor , respectively), and nitrogen stable isotopes (δ 15 N).…”
Section: Resident Speciessupporting
confidence: 93%
“…We considered T. truncatus, S. frontalis, S. guianensis and P. blainvillei as resident species, based on available information resulting from sightings, strandings and accidental catches along the south-eastern coast of Brazil (Santos et al, 2010(Santos et al, , 2017(Santos et al, , 2019, as well as recent results on local cetacean niche modelling (Figueiredo et al, 2020). The large Euclidean distance between T. truncatus and the remaining odontocetes is related to its significantly higher δ 15 N values in comparison to the remaining cetacean species.…”
Section: Resident Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…The results presented here share spectral and temporal details of the echolocation and burst pulse clicks of P. blainvillei from coastal waters in the southeastern Atlantic Ocean. When modeling the niche of local cetaceans, Figueiredo et al (2020) warned that onboard sightings were not the best tool when considering P. blainvillei , which was not sighted in an area of a large number of incidental captures (see Campos et al, 2020) where they are camouflaged by turbid waters. Thus, our descriptions of P. blainvillei acoustic parameters provide new tools for further investigations of this species occurrence in local waters using PAM.…”
Section: Figurementioning
confidence: 99%